OFR-6-95 Economic Feasibility Of Mining In The Ketchikan Mining District, Alaska - James R. Coldwell (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Mining and processing cost analyses were conducted by the U.S. Bureau of Mines on massive sulfide copper-zinc and low sulfide vein gold deposit types that may be found in the Ketchikan Mining District. Reserves and recoverable metal values (RMV) needed to make these deposits economically viable were modeled. Methods for estimating ore grades and required RMV are presented. Economic modeling for massive sulfide deposits indicated the RMV necessary for a 15% Discounted Cash-Flow Rate-Of-Return (DCFROR) for an underground cut-and-fill mine ranged from $137/mt for a 6,100 mtpd on-site milling operation to $526/mt for a 450 mtpd off-site milling operation. On-site milling was always less costly than off-site milling. Economic modeling for low sulfide vein gold deposits indicated the RMV necessary for a 15% DCFROR for an open-pit mine, off-site mining operation ranged from $S4/mt at 2,900 mtpd to $71/mt at 360 mtpd, and from $49/mt at 2,900 mtpd to $100/mt at 360 mtpd for an on-site milling operation. Off-site milling was less costly than on-site milling until production exceeded approximately 1,700 mtpd. Then, economies of scale reduced operating costs enough to offset the higher capital costs required for on-site milling.